New records of the larval forms Cerataspis monstrosa and Amphionides reynaudii (Crustacea: Decapoda) from the western tropical Atlantic - Lira, Simone Maria De Albuquerque; Santana, Claudeilton Severino De; Lima, Cynthia Dayanne Mello De; Montes, Manuel De Jesus Flores; Schwamborn, Ralf (Zootaxa, 2017)
The current biogeographic and taxonomic knowledge on decapod larvae in tropical oceans is still very incomplete, in spite of their huge ecological and socio-economic importance. The present study reports two new records for decapod larval forms in pelagic environments off oceanic islands in the western tropical Atlantic, and provides detailed diagnoses and images of these larvae. Samples were taken from July 2010 to November 2014 using neuston, bongo and WP-2 nets at three localities: St. Peter and St. Paul’s Archipelago (SPSP), Rocas Atoll (RA) and Fernando de Noronha Archipelago (FN). The larval forms Cerataspis monstrosa (Gray, 1828) and Amphionides reynaudii (H. Milne Edwards, 1832) were recorded around these areas, constituting the first record for these oceanic islands. Out of 121 samples analyzed, one specimen of C. monstrosa (Mysis II) was found off FN, and 20 specimens of A. reynaudii in nine distinct stages (Mysis II, IV, VI, VII, VIII, IX, X, XI, XII) were found off SPSP, RA and FN.